The Effect of Compensation and Work Environment on Employee Satisfaction at PT. Veneta Indonesia - Farida Nuraini; Asep Sutarman; Edi Setiawan; Luthpiyah Juliandara (Business Review and Case Studies, 2022)
One of the factors that influence employee job satisfaction is the amount of compensation received by employees every month and a comfortable work environment. The purpose of this study was to analyze the influence of compensation and work environment in increasing employee job satisfaction at PT. Indonesian Veneta. The population in this study were all employees of PT. Veneta Indonesia as many as 63 people, using a census sampling technique where all of the population is used as a sample. Data analysis processing techniques used are descriptive analysis, data quality test, classical assumption test, multiple linear regression analysis, correlation coefficient analysis, and analysis of the coefficient of determination. Then the data is processed using multiple linear regression analysis and processed using SPSS version 22.0. The results of the study with a level of 5% found that Compensation has a positive and significant effect on Employee Job Satisfaction, Work Environment has a positive and significant effect on Employee Job Satisfaction, and Compensation and work environment simultaneously have a significant effect on Employee Job Satisfaction. The results of the study show that giving financial compensation on time and providing additional benefits which are of course in accordance with applicable regulations can increase employee job satisfaction. Keywords: employee job satisfaction, compensation, work environment, veneta indonesia, multiple linear regression